Low-level laser therapy (808 nm) contributes to muscle regeneration and prevents fibrosis in rat tibialis anterior muscle after cryolesion - Assis, Lívia (2012)
Muscle regeneration is a complex phenomenon, involving replacement of damaged fibers by new muscle fibers. During this process, there is a tendency to form scar tissue or fibrosis by deposition of collagen that could be detrimental to muscle function. New therapies that could regulate fibrosis and favor muscle regeneration would be important for physical therapy. Low-level laser therapy (LLLT) has been studied for clinical treatment of skeletal muscle injuries and disorders, even though the molecular and cellular mechanisms have not yet been clarified. The aim of this study was to evaluate the effects of LLLT on molecular markers involved in muscle fibrosis and regeneration after cryolesion of the tibialis anterior (TA) muscle in rats. Sixty Wistar rats were randomly divided into three groups: control, injured TA muscle without LLLT, injured TA muscle treated with LLLT. The injured region was irradiated daily for four consecutive days, starting immediately after the lesion using an AlGaAs laser (808 nm, 30 mW, 180 J/cm(2); 3.8 W/cm(2), 1.4 J). The animals were sacrificed on the fourth day after injury. LLLT significantly reduced the lesion percentage area in the injured muscle (p<0.05), increased mRNA levels of the transcription factors MyoD and myogenin (p<0.01) and the pro-angiogenic vascular endothelial growth factor (p<0.01). Moreover, LLLT decreased the expression of the profibrotic transforming growth factor TGF-β mRNA (p<0.01) and reduced type I collagen deposition (p<0.01). These results suggest that LLLT could be an effective therapeutic approach for promoting skeletal muscle regeneration while preventing tissue fibrosis after muscle injury.